The impact of China’s economic restructuring on Southeast Asia: An investment perspective - Zhang, M.; Li, R. (Institute of China Studies, University of Malaya, 2017)
China’s economic growth in 2015 has fallen to 6.9% from an unrivalled average of 10% between 2002 and 2014. While the global economy is feeling the impact of China’s economic restructuring, a change of such a magnitude in China has created a great impact on Southeast Asia, which is intensively involved in trade and investment with China. By analyzing macroeconomic data, we find no indication that China’s outward investment in Southeast Asia was immediately shocked by China’s New Normal. Instead, in an economically challenging era after 2007, Chinese OFDI in ASEAN has increased significantly. Though Chinese OFDI in Southeast Asia is distributed unevenly in geographical and industrial terms, the analysis of regional and sectorial distribution has reflected a paradigm shift of China’s economy from an export oriented to an investment driven growth. The rising wave of Chinese investment in ASEAN can be understood by China’s dilemma of over-capacity in some manufacturing sectors. Given the increasing production cost which has significantly reduced cost advantages of Chinese manufacturing, the rapid growth of Chinese outward investment is not only a result of a single firm’s strategic shift to relocate to seek higher returns. It is rather a collective reaction of Chinese firms to the challenging business environment in China’s domestic market.